2017
DOI: 10.1080/10872981.2017.1291869
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the suicide intervention skills of emergency medical services providers

Abstract: Background: Lithuania currently has the highest suicide rate in Europe and the fifth highest worldwide. Aims: To identify the factors that influence the suicide intervention skills of emergency medical services (EMS) providers (doctors, nurses, paramedics). Method: Two hundred and sixty-eight EMS providers participated in the research. The EMS providers were surveyed both prior to their training in suicide intervention and six months later. The questionnaire used for the survey assessed their socio-demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
0
12
0
5
Order By: Relevance
“…Given that ambulance staff may be at the scene of death for a prolonged period before other services arrive in instances of suicide, evidence-based training in critical incident management (Everly and Mitchell, 1997;Maple et al, 2019) is needed. Other qualitative research (Foggin et al, 2016) has demonstrated the extent to which even second responders such as GPs find facing the intense distress or anger of people bereaved by suicide difficult; it has also been emphasized that first responders need continuous training in suicide intervention and skills for coping with trauma-related stress (Lygnugaryte-Griksiene et al, 2017).…”
Section: Contribution To Current Understandingmentioning
confidence: 99%
“…Given that ambulance staff may be at the scene of death for a prolonged period before other services arrive in instances of suicide, evidence-based training in critical incident management (Everly and Mitchell, 1997;Maple et al, 2019) is needed. Other qualitative research (Foggin et al, 2016) has demonstrated the extent to which even second responders such as GPs find facing the intense distress or anger of people bereaved by suicide difficult; it has also been emphasized that first responders need continuous training in suicide intervention and skills for coping with trauma-related stress (Lygnugaryte-Griksiene et al, 2017).…”
Section: Contribution To Current Understandingmentioning
confidence: 99%
“…Medicinske sestre delujejo na različnih področjih, kjer prepoznavajo, posredujejo in vrednotijo stanje Tabela 2: Razporeditev kod po kategorijah Lynch, et al, 2008;Chan, et al, 2009;Meerwijk, et al, 2010;Bregar, 2012;Sakinofsky, 2014;Bolster, et al, 2015;Hagen, et al, 2017;Seixas Santos, et al, 2017;Jansson & Hällgren Graneheim, 2018 Cutcliffe & Stevenson, 2008;Lynch, et al, 2008;Lakeman, 2010;Bregar, 2012;Sun, et al, 2013;Sakinofsky, 2014;Sellin, et al, 2017;Seixas Santos, et al, 2017;Hagen, et al, 2017Hagen, et al, , 2018 Palmieri, et al, 2008;Chan, et al, 2009;Meerwijk, et al, 2010;Bolster, et al, 2015;Lygnugaryte-Griksiene, et al, 2017;Jansson & Hagen, et al, 2018;Hällgren Graneheim, 2018;Wang, et al, 2018 Ukrepi za izboljšanje obravnave in preprečevanje samomora Izobraževanje in usposabljanje na področju samomorilno ogroženih pacientov Povečanje samozavesti medicinskih sester Razvoj preventivnih praks Zagotavljanje podpore medicinskim sestram pri obravnavi samomorilno ogroženih pacientov Izboljšanje načina spopadanja medicinskih sester s samomori pacientov Preprečevanje izgorevanja medicinskih sester Palmieri, et al, 2008;Chan, et al, 2009;Bolster, et al, 2015;Griksiene, et al, 2017;Seixas Santos, et al, 2017;Lygnugaryte-Jansson & Hällgren Graneheim, 2018;…”
Section: Diskusijaunclassified
“…7The fact that EMS providers receive adequate training on this issue is also considered as a crucial point in terms of preventing suicides. (4) In our knowledge, although various studies have been published in some of the provinces and territories of our country for the use of EMS for suicide-related emergencies, a study reflecting the general state has not been published yet. Therefore, the purpose of this study is to investigate the use of EMS by geriatric patients due to suicide.…”
Section: Introductionmentioning
confidence: 99%